Economic Impacts of Drought on the Florida Environmental Horticulture Industry - Alan W. Hodges; John J. Haydu (EDIS)
Written by Alan W. Hodges, PhD, and John J. Haydu, PhD. University of Florida, Institute of Food & Agricultural Sciences Food & Resource Economics Department, Gainesville. Revised May 19, 2003.